Eosinophils at diagnosis are elevated in amyotrophic lateral sclerosis - Yang, Jing; Liu, Tingting; Zhang, Lei; Li, Xin; Du, Feng Ping; Liu, Qi; Dong, Hui; Liu, Yaling (Frontiers in Neurology, 2023)
Introduction Amyotrophic lateral sclerosis (ALS) is a rare, devastating neurodegenerative disease that affects upper and lower motor neurons. To date, no effective treatment or reliable biomarker for ALS has been developed. In recent years, many factors have been proposed as possible biomarkers of ALS; however, no consensus has been reached. Therefore, a reliable biomarker is urgently needed. Eosinophils may play a crucial role in healthy humans and diseases, and serve as a biomarker for many chronic diseases. Methods Routine blood test results were collected from 66 healthy controls and 59 patients with ALS. The percentages and total numbers of each cell population were analyzed, and the correlation between these indicators and patient ALS functional rating scale–revised (ALSFRS-R) score or disease progression rate (ΔFS score) was analyzed. Results Compared to healthy controls, the number of blood leukocytes, neutrophils, monocytes, and basophils was significantly decreased in patients with ALS (p = 0.002, p = 0.001, p = 0.049, and p < 0.0001, respectively). There was an increase in the number of eosinophils (p < 0.0001), but no difference in the number of lymphocytes between patients with ALS and healthy controls was found (p = 0.563). Compared to healthy controls, the percentage of neutrophils was decreased and the percentage of lymphocytes and eosinophils was increased in patients with ALS (p = 0.01, p = 0.012, and p = 0.001, respectively). There was no difference between patients with ALS and healthy controls in the percentage of monocytes and basophils (p = 0.622 and p = 0.09, respectively). However, only the percentage and number of eosinophils had a correlation with the ΔFS score. Further multivariate analysis revealed a significant correlation between the disease duration, eosinophil count and percentage, and the disease progression rate (p < 0.0001, p = 0.048, and p = 0.023, respectively). The neutrophil-to-eosinophil ratio (NER), lymphocyte-to-eosinophil ratio (LER), and monocyte-to-eosinophil ratio (MER) were significantly lower in patients with ALS than in healthy controls. However, only the LER was significantly correlated with the ΔFS score. Conclusion These observations implicate neutrophils, lymphocytes, and eosinophils as important factors, and increasing eosinophil counts were negatively correlated with the ΔFS score in patients with ALS.